Relative anti-caries efficacy of 1100, 1700, 2200, and 2800 ppm fluoride ion in a sodium fluoride dentifrice over 1 year - BERGMAN, Ronald A. (Blackwell Synergy, 2001)
There is limited evidence from clinical trials on the dose response of sodium fluoride dentifrices at concentrations above 1100 ppm fluoride ion, with respect to caries efficacy